Sudden death in athletes [Sporcularda ani ölüm] - (:unkn) unknown (Kare Publishing, 2006)
Increasing number of children and adolescents are involved in sportive activities in recent years. However, sudden death of some young athletes causes anxiety among the parents and the society. About 95% of sudden deaths are related to the cardiac causes. The most common disease states are hypertrophic cardiomyopathy, arrhythmogenic right ventricle displasia, and congenital abnormalities of the coronary arteries. In addition to heart disease whether diagnosed or not, the effect of performance enhancing substances must also be considered. In order to prevent sudden death, standard screening programs should be applied to all athletes. A detailed history including the family history, physical examination and electrocardiography would provide exclusion of many cardiac disorders.
Keywords: Athletes heart; Sports death; Sudden death